Challenging the ability intuition: From personal to extended to distributed belief‐forming processes. - Shieber, Joseph (Philosophical Issues, 2022)
Much of what we know results from information sources on which we epistemically rely. This fact about epistemic reliance, however, stands in tension with a very powerful intuition governing knowledge, an intuition that Pritchard (e.g., 2010) has termed the "ability intuition," the idea that a believer's "reliable cognitive faculties are the most salient part of the total set of causal factors that give rise to [their] believing the truth" (Vaesen, 2011, p. 518; compare Greco, 2003; 2009; 2010). In this paper I suggest that this tension may indeed be ineliminable. I proceed by canvassing some representative attempts to reconcile epistemic reliance and the ability intuition. In doing so, I suggest that all of these attempts founder on one or the other of two elements of what I've previously described (Shieber, 2013, 2015) as a "personalist presumption" in discussions of social epistemology: an excessive focus on (i) reliability filters within the persons who are the recipients of information or (ii) on reliable truth‐tracking and ‐conveying abilities in the persons who are the transmitters of information. In conclusion, I suggest how best to resolve the tension: by abandoning the ability intuition.